An updated system for the targeted mutagenesis of the psbDI:psbC operon in Synechocystis sp. PCC 6803: mutations targeting Asp460 in CP43 of Photosystem II reduce oxygen-evolving activity and perturb electron transfer in the quinone-Fe-acceptor complex. Issue 4 (1st October 2020) - Khaing, Ei Phyo; Zhong, Victor; Eaton-Rye, Julian J.
ABSTRACT: The cyanobacterium Synechocystis sp. PCC 6803 is widely used as a model organism to study Photosystem II (PS II) of oxygenic photosynthesis. In response to inherent genetic instability in cyanobacteria we re-sequenced our strain of Synechocystis sp. PCC 6803, designated as Glucose Tolerant Otago 1 (GT-O1), to establish its genomic background [Morris JN, Crawford TS, Jeffs A, Stockwell PA, Eaton-Rye JJ, Summerfield TC. 2014. New Zealand Journal of Botany. 52:36–47]. Here we have constructed a mutagenesis system to enable us to study roles of the D2 and CP43 PS II reaction centre proteins in the GT-O1 strain. A ΔDIC/ΔDII deletion mutant was assembled in which the psbDI/psbC operon encoding D2 and CP43 was replaced by a chloramphenicol-resistance cassette and psbDII, encoding a second copy of D2, was replaced with a kanamycin-resistance cassette. A DIC + /DII – control strain was constructed by reintroducing the psbDI/psbC operon under selection provided by a spectinomycin-resistance cassette. In this system mutations can be introduced following in vitro mutagenesis of the psbDI/psbC operon. To test our system, we introduced mutations at the CP43 residue Asp460 which is hydrogen bonded to Arg-24 and Arg-28 of the PsbT low-molecular-weight subunit of PS II that is found at the monomer–monomer interface of the PS II dimeric complex in the thylakoid membrane. While the control strain showed a similar phenotype to wild type our CP43 mutants (D460A, D460E and D460N) exhibited a reduction of oxygen-evolving activity and alteration in electron transfer between the primary (QA ) and secondary (QB ) plastoquinone electron acceptors of PS II.